PATTERNS OF RATIONALITY IN NORDIC LANGUAGE TEACHERS’ VIEWS ON SECOND LANGUAGE - Ivanishcheva, Olga; von Post, Christina; Räihä, Helge (Revista Inclusiones, 2020)
The purpose of the work is to investigate linguistic methods for detailed analyzes of rationality and to explore their usefulness, in this current study by analyzing how Nordic language teachers rationalize their views on second language The research methods consist of explorative qualitative analysis of focus group interviews by using linguistic markers of different rationality forms on a word level. The material consists of focus group interviews of second-language teachers in Finland, Denmark and Sweden. The result show that all interviewed teachers in the Nordic countries favored a monolingual view on second language learning, which is in opposition to the national curricula in one of the Nordic countries that advocates multilingualism, and in addition, despite that one of the countries has two national languages.